Genetic Parameter Analysis of Indicator Traits of Gastrointestinal Nematode Infection in Sheep Breeds - Selvam, R. (International Journal of Bio-resource and Stress Management, 2022)
This study was undertaken with an aim to analyse the indicator traits of gastrointestinal nematode infection viz., FAMACHA score, FEC and PCV and to estimate the correlation among these traits. This study was carried out in a total of 100 sheep, 50 of each Kilakarsal and Vembur sheep breeds. The data were analysed using a mixed model least-squares analysis for fitting constants and the relationship among traits were estimated. The overall least-squares mean for FAMACHA scores were 2.88±1.144 and 2.9±0.151; FEC were 792±121.448 and 767.0±100.576; PCV were 26.38±0.199 and 26.14±0.189, in Kilakarsal and Vembur sheep, respectively. The Pearson Correlations study revealed that there is highly significant (P<0.01) positive correlation between FAMACHA scores and FEC in Kilakarsal (0.835**) and Vembur (0.863**) sheep, But PCV is highly significantly negatively correlated with FAMACHA scores (Kilakarsal: -0.843**and Vembur: -0.883**) and FEC (Kilakarsal: -0.874** and Vembur: -0.924**). According to Spearman’s rho correlations analysis, FAMACHA scores (Kilakarsal: -0.802** and Vembur: -0.893**) and FEC (Kilakarsal: -0.811** and Vembur: -0.920**) had negative associations with PCV which are highly significant (p<0.01) and the FAMACHA scores exhibited a highly significant positive association with FEC with values of 0.957** and 0.954** in Kilakarsal and Vembur sheep, respectively. It is concluded that the FAMACHA score, FEC, PCV are the best indicator traits for gastrointestinal nematode infection, especially Haemonchus contortus is major disease causing pathogen. The correlation analysis of indicator traits will help in selection of genetically resistant animals against gastrointestinal infection.